MENGURANGI KEJADIAN DISMENORE DENGAN MENJAGA KENORMALAN KADAR HEMOGLOBIN - Nana Aldriana; Rahmi Fitria; Eka Yuli Handayani; Rahmawati (Fakultas Ilmu Kesehatan, 2024)
The dysmenore consists of complex symptoms of lower stomach cramps that spread to the back or legs and are usually accompanied by gastrointestinal symptoms and neorological symptoms such as common weakness. Approximately 50% of menstruated women experience dysmenorrhea, and 10% have severe symptoms that require bed rest. Women with dysmenore will have an impact on women's health and productivity. Women with dysmenore have more holiday days and have less performance in school. In addition to that, it's an early symptom of a female reproductive disorder. Many factors cause of the dysmenorrhea include psychological factors, endocrine factor, sevikalys canalical clusion factor, allergic factor, constitutional factors such as anemia and disease bear. Anemia is a state of decreased amount of erythrocytes or hemoglobin from normal value in the blood so it cannot fulfill its function to carry enough O2 to the peripheral tissue so that the delivery of o2 to the tissue decreases.The purpose of this study is to find out the relationship of hemoglobin levels with dismenore of the students Pasir Pengaraian university, so that by maintaining the normality of hemoglobin levels can lower the occurrence of dismenore. Method of research is analytic quantitative with a cross sectional approach. Sample in this study is the entire first year students of health science faculty Pasir Pengaraian university which amount 60 respondens. Data analysis is univitarian and bivariatically used the chi-square test. Studies obtained a value of p = 0.001 with value OR = 2,900 means there's a significant connection between hemoglobin levels and the dysmenore incident of students at Pasir Pengaraian University. The conclusion of the dysmenore event can be reduced by keeping hemoglobin at normal levels. Suggest that a student maintains a nutrition intake to ensure that hb is within normal limits.